1997
DOI: 10.1159/000177322
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Function in Insulin-Dependent and in Non-Insulin-Dependent Diabetic Patients: Radionuclide Assessment

Abstract: The aim of this study was to compare, by gated radionuclide angiography, systolic and diastolic ventricular function in insulin-dependent (IDDM) and non-insulin-dependent (NIDDM) diabetic patients without overt cardiovascular disease. The study population consisted of 20 IDDM patients (15 male, 5 female; 40.7 ± 10.3 years), 14 NIDDM patients (9 male, 5 female; 47.0 ± 7.5 years) and 12 healthy subjects (7 male, 5 female; 41.5 ± 6.3 years) as a control (C) group. The duration of diabetes (DD) and glycosylated he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 15 publications
0
21
0
3
Order By: Relevance
“…11 Multiple trials based on CTLA4-Ig are currently ongoing, 31,32 with almost 2000 individuals already treated and an overall rate of side effects comparable to the placebo arm. 11,33 We acknowledge that different limitations are present in our study. First, we did not demonstrate a major salutary effect of CTLA4-Ig on DN.…”
Section: Discussionmentioning
confidence: 97%
“…11 Multiple trials based on CTLA4-Ig are currently ongoing, 31,32 with almost 2000 individuals already treated and an overall rate of side effects comparable to the placebo arm. 11,33 We acknowledge that different limitations are present in our study. First, we did not demonstrate a major salutary effect of CTLA4-Ig on DN.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown a correlation between glycemic control and LVDD, with associated improvement in cardiac function after adequate treatment (7,(15)(16)(17). However, other studies have found no such correlation (4,6,11,18).…”
mentioning
confidence: 99%
“…A systolic dysfunction in normotensive diabetic patients was not clearly shown, although a decrease in fractional shortening and an increase of left ventricular mass were reported (3). Abnormality in diastolic dysfunction has been more uniformly observed in asymptomatic diabetic patients with an altered diastolic filling, as shown by impaired values of peak filling rate and timeto-peak filling rate (4). The relationship between diastolic dysfunction and metabolic control in type 1 diabetic patients is still a matter of debate (4).…”
mentioning
confidence: 99%
“…Abnormality in diastolic dysfunction has been more uniformly observed in asymptomatic diabetic patients with an altered diastolic filling, as shown by impaired values of peak filling rate and timeto-peak filling rate (4). The relationship between diastolic dysfunction and metabolic control in type 1 diabetic patients is still a matter of debate (4). Studies involving the reversal of diabetic cardiomyopathy after tight glycemic control in type 1 diabetes are lacking.…”
mentioning
confidence: 99%